A SYSTEMATIC INVESTIGATION OF THE EFFECTS OF VARIOUS BULBOUS BOWS ON RESISTANCE OF FISHING BOATS - Saral, Dursun; Aydin, Muhsin; Kose, Ercan (UNIV ZAGREB FAC MECHANICAL ENGINEERING & NAVAL ARCHITECTURE, 2018)
In this study, Delta (Delta) Nabla (del) and Elliptical (O) shaped bulbs are implemented to ITU Fishing Boats Series hull forms of 148/3, 148/4, 148/8 and 148/9 in order to determine the most appropriate bulbous bow for fishing vessels. Initially, in defined Fn values, Computational Fluid Dynamics (CFD) analyses on four main forms are performed by using Realizable k-epsilon Model and Volume of Fluid (VOF) method. The total resistance values obtained by the CFD analyses and by the existing test results via Froude and Hughes methods are compared and examined. Thus, the method and reference values of CFD analyses are determined for the hull forms with bulbs which do not have test results. Subsequently, the CFD results of frictional resistance, pressure resistance and total resistance values for actual hulls and hulls with bulbs are compared. Following the examination of results in terms of C-B, L/B and bulb types, it is determined that the elliptical bulb type is the most suitable bulb type for the fishing vessels.
Keywords: Fishing Boat; Bulbous Bow; Computational Fluid Dynamics (CFD); Resistance; DESIGN; Engineering